2021
DOI: 10.3390/jcm10020252
|View full text |Cite
|
Sign up to set email alerts
|

Time Points for Gonadotropin-Releasing Hormone Stimulation Test Results in Korean Children

Abstract: The gold standard for the laboratory diagnosis of central precocious puberty is based on the measurement of luteinizing hormone (LH) after gonadotropin-releasing hormone (GnRH) stimulation. We sought to investigate the laboratory data for GnRH stimulation testing using samples collected from Korean children at different time points. Sampling times were at the basal time point (0) and 15, 30, 45, 60, 90, and 120 min after GnRH stimulation. Pubertal response was defined as occurring when the peak LH concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Although our observations were limited to a small cohort of pediatric patients, several studies have confirmed these results. For example, Choi et al analyzed a group of 1,958 children, of whom 1,232 had a subsequently confirmed diagnosis of CPP, and demonstrated that the combined hormonal dosage at 45 and 60 min from the start of the GnRH test showed a sensitivity of 99.1% and a specificity of 100% in identifying the LH peak for all children, suggesting a possible reduction in blood sampling during the GnRH test (5). Similar results were reported by Cao et al, who studied 1,492 children with suspected CPP and suggested the possibility of a single blood sample at 60 min and showed that even the basal LH dosage, when higher than a certain cutoff (above 0.535 mIU/L), could be used to diagnose CPP without a stimulus test (6).…”
Section: Discussionmentioning
confidence: 99%
“…Although our observations were limited to a small cohort of pediatric patients, several studies have confirmed these results. For example, Choi et al analyzed a group of 1,958 children, of whom 1,232 had a subsequently confirmed diagnosis of CPP, and demonstrated that the combined hormonal dosage at 45 and 60 min from the start of the GnRH test showed a sensitivity of 99.1% and a specificity of 100% in identifying the LH peak for all children, suggesting a possible reduction in blood sampling during the GnRH test (5). Similar results were reported by Cao et al, who studied 1,492 children with suspected CPP and suggested the possibility of a single blood sample at 60 min and showed that even the basal LH dosage, when higher than a certain cutoff (above 0.535 mIU/L), could be used to diagnose CPP without a stimulus test (6).…”
Section: Discussionmentioning
confidence: 99%
“…The public HIRA database contains all reimbursed lipoprotein(a) tests performed in local clinics, hospitals, and tertiary university hospitals, which might have different population characteristics, such as comorbidities. For example, the prevalence of precocious puberty, one reason for visiting local clinics and hospitals, is higher in girls than in boys [ 23 ]. Considering the possible association between hyperlipidemia and precocious puberty, this might result in differences between girls and boys who tested for serum lipoprotein(a) levels [ 24 ]; however, detailed clinical information was limited for this study.…”
Section: Discussionmentioning
confidence: 99%